The Use Of Youtube Media In Improving Listening And Speaking Skills In UIN Kiai Haji Achmad Siddiq Jember - Sinta Bella; Mokhammad Miftakhul Huda (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2022)
Listening and speaking skills are two of the four Arabic language skills that are highly influential in developing the language. Both of these skills can be successful if students continue to practice and practice, but these two activities can be done if supported by adequate environmental facilities. Therefore, YouTube media tries to answer the limitations of the environment experienced by students. This study aims to describe the use of YouTube media to increase students’ listening and speaking skills. The method used is the qualitative research method with a descriptive approach. This study revealed that media YouTube delivered improvements to students’ listening and speaking skills. Although due to the limitations of the media, still have a record, including not all can use this media if you do not have internet access. As well as the unavailability of automatic translation. Maharah kalam dan maharah istima’ adalah dua dari empat keterambilan bahasa Arab yang sangat mempengaruhi dalam perkembangan berbahasa. Kedua keterampilan ini bisa dinggap berhasil jika siswa terus melakukan latihan dan praktek, tetapi dua kegiatan tersebut bisa dilakukan jika didukung dengan fasilitas lingkungan yang memadai. Karena itu, media YouTube berusaha menjawab keterbatasan lingkungan yang dialami siswa. Tujuan penelitian ini untuk mendeskripsikan pemanfaatan media YouTube untuk peningkatan maharah kalam dan maharah istima’ mahasiswa. Metode yang digunakan adalah metode penelitian kualitatif dengan pendekatan deskriptif. Penelitian ini mengungkap bahwa media YouTube pada dasarnya memberikan peningkatan terhadap maharah kalam dan maharah istima’ mahasiswa. Meskipun karena keterbatasan media tersebut, tetap memiliki catatan, di antaranya tidak semua bisa menggunakan media ini jika tidak memiliki akses internet. Serta tidak tersedianya translate otomatis.